HIV vasculopathy. (24th August 2015) - Hale, Andrew T.; Longenecker, Chris T.; Jiang, Ying; Debanne, Sara M.; Labatto, Danielle E.; Storer, Norma; Hamik, Anne; McComsey, Grace A.
<x xml:space="preserve">Abstract</x> Objective: To determine the relationships between Krüppel-like factors (KLF) 2 and 4, immune-activation, and subclinical vascular disease in HIV-infected patients on antiretroviral therapy (ART). Design: Double-blind, randomized, placebo-controlled trial. Methods: We studied 74 HIV-infected adults on ART enrolled in a randomized clinical trial of statin therapy. KLF2 and KLF4 gene expression was measured by quantitative PCR from peripheral blood mononuclear cells (PBMCs) at baseline and after 24 weeks of 10 mg daily rosuvastatin or placebo. At the same time points, T-cell and monocyte activation were assessed by flow cytometry and vascular health was assessed by cardiac computed tomography and carotid ultrasound. Results: KLF4 expression was negatively correlated with duration of ART (r = −0.351, P = 0.004) and positively correlated with measures of immune activation: proinflammatory monocytes [CD14+CD16+ (r = 0.343, P = 0.003)], patrolling monocytes [CD14dimCD16+ (r = 0.276, P = 0.017)], and activated CD8+ T-lymphocytes [CD8+DR+CD38+ (r = 0.264, P = 0.023)]. KLF2 expression was negatively correlated with subclinical atherosclerosis: mean–mean common carotid artery intima–media thickness (r = −0.231, P = 0.048), mean–max carotid artery intima-media thickness (r = −0.271, P = 0.020), and coronary artery calcium score (r = −0.254, P = 0.029). There were no statistically significant changes in KLF2/4 expression in PBMCs after 24 weeks of rosuvastatin. Conclusion: Expression of KLF4 in PBMCs positively correlates with cellular markers of immune activation, whereas KLF2 expression negatively correlates with markers of subclinical atherosclerosis in this HIV-infected population on ART. Additional studies are needed to determine if targeted interventions might alter KLF2/4 expression to reduce inflammation and vascular risk in humans.